NUMERICAL SIMULATION OF THERMAL CONDITION OF A LOW CURRENT ELECTRIC CONTACT: n/a (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2021)
Electrical contacts may include various sub-systems or wiring harnesses connected via detachable connectors, which depend on physical contacts for electrical connectivity. Electrical contacts range from high, medium, to low currents depending on usage. However, in real-life condition, electrical contact characteristics, especially at the interface, undergoes a gradual change which can be due to corrosion, temperature variation, aging, strained harnesses, discontinuities induced by vibration, etc. These changes introduce additional parasitic circuits in the system. Moreover, in some cases where the contact resistance increases due to electrical losses, the local temperature may increase, thereby accelerating contact degradation. This paper presents a numerical analysis of the variation of temperature of a simple low current contact model having a thin oxide film layer at the interface, which serves as the aging factor using the finite element method (FEM).
Keywords: Low current electric contact; Thermal stability; Numerical simulations